2005
DOI: 10.1158/0008-5472.499.65.2
|View full text |Cite
|
Sign up to set email alerts
|

The Serum Glycoprotein Fetuin-A Promotes Lewis Lung Carcinoma Tumorigenesis via Adhesive-Dependent and Adhesive-Independent Mechanisms

Abstract: Fetuin-A is a serum glycoprotein in the cystatin family associated with the regulation of soft tissue calcification. We tested the role of systemic fetuin in tumor cell growth and metastasis by injecting Lewis lung carcinoma (LLC) cells into fetuin-A null and their wild-type (WT) littermate control C57BL/6 mice via the tail vein, s.c., and intrasplenic routes. In the experimental metastasis assay, the lungs of the WT mice were filled with metastatic nodules, whereas the lungs of the fetuin-A null mutant mice w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 56 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…AHSG is synthesized in the adult liver and many other organs during embryogenesis. The protein is selectively accumulated in the bone matrix and inhibits pathological mineralization due to its high affinity to calcium, barium and hydroxyapatite. Recent studies have shown that AHSG regulates immune response, cell adhesion, promotes growth and inhibits tumor progression. ANG, the fifth member of the pancreatic ribonuclease superfamily, is a tRNA-specific ribonuclease that abolishes protein synthesis by specifically hydrolyzing cellular tRNAs and triggers a number of biological processes, including cell migration, invasion, proliferation, angiogenesis and formation of tubular structures. CST3, one of the extracellular type II cystatins, is a low molecular-weight protein that acts as a strong inhibitor of cysteine peptidases of the papain family . CST3 proteins are expressed in various tissues, where they regulate normal proteolysis and participate in disease pathology. , Numerous studies suggest that CST3 participates in multiple steps of cancer progression, such as transformation of cells to a malignant state, tumor growth, invasion and metastasis .…”
Section: Resultsmentioning
confidence: 99%
“…AHSG is synthesized in the adult liver and many other organs during embryogenesis. The protein is selectively accumulated in the bone matrix and inhibits pathological mineralization due to its high affinity to calcium, barium and hydroxyapatite. Recent studies have shown that AHSG regulates immune response, cell adhesion, promotes growth and inhibits tumor progression. ANG, the fifth member of the pancreatic ribonuclease superfamily, is a tRNA-specific ribonuclease that abolishes protein synthesis by specifically hydrolyzing cellular tRNAs and triggers a number of biological processes, including cell migration, invasion, proliferation, angiogenesis and formation of tubular structures. CST3, one of the extracellular type II cystatins, is a low molecular-weight protein that acts as a strong inhibitor of cysteine peptidases of the papain family . CST3 proteins are expressed in various tissues, where they regulate normal proteolysis and participate in disease pathology. , Numerous studies suggest that CST3 participates in multiple steps of cancer progression, such as transformation of cells to a malignant state, tumor growth, invasion and metastasis .…”
Section: Resultsmentioning
confidence: 99%
“…48 The concentration of AHSG in human serum is ∼1.5 mg/mL during fetal development and ∼0.5 mg/mL in adult blood. 49 AHSG is mainly synthesized and secreted by the liver (>95%) and the rest by adipocyte, kidney, placenta, tongue, etc. Elevated circulating Fetuin A is associated with several illnesses such as type 2 diabetes mellitus, obesity, non alcoholic fatty liver disease (NAFLD), dyslipidemia, artherosclerosis, cardiovascular disease, etc.…”
Section: Introductionmentioning
confidence: 99%
“…Cancer cells have surface receptor Annexin 2 and Annexin 6, which serve as receptors for AHSG. 49 As a result, the glycoprotein can enter the breast carcinoma cells and helps their growth. 52 Thus, AHSG directed cell imaging may help in detecting the role of the particular protein inside the cell.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations